Summer program: management seminar: FISAT@FBM, UiТM - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
On 7th March 2024, a welcome was extended to inbound students and lecturers from the Federal Institute of Science and Technology (FISAT), India, to the Faculty of Business and Management at UiTM Kampus Puncak Alam. The delegation comprised 98 postgraduate students and four lecturers, led by Dr. Anoo Anna Antony. A module titled "Entrepreneurship Strategic Management" was delivered by an experienced lecturer, Dr. Gouri Dominic. A productive discussion took place between the two universities, covering potential collaborations and sharing insights on the current business culture of both countries. Gratitude was expressed to FISAT for choosing UiTM and the faculty for this engagement.